Parametric Design of Parabolic Reflector Antenna with Switchable Cosecant-Squared Pattern - (:unkn) unknown (APPLIED COMPUTATIONAL ELECTROMAGNETICS SOC, 2011)
This paper deals with the parametric analysis of multi-beam parabolic reflector antennas employed for air and coastal surveillance radars. Novel designs are introduced to obtain electronically switchable cosecant-squared and pencil beam radiation patterns, without making any changes on the reflector geometry. The analytical regularization method (ARM) is used as a fast and accurate way to solve the problem of E-polarized wave diffraction by parabolic shaped perfectly electrical conductive (PEC) cylindrical reflector with finite thickness. The numerical procedure is initially verified by the analytical and numerical methods, and the calculated radiation characteristics are presented for the proposed antenna configurations.
Keywords: Analytical regularization method; cosecant-squared radiation pattern; multi-source horn; parabolic reflector antenna; APERTURE ILLUMINATION; RADIATION